Corrosion of copper alloys in KOH, NaOH, NaCl, and HCl electrolyte solutions and its impact to the mechanical properties - Ida Hamidah, .; Agus, Solehudin; Aam, Hamdani; Lilik, Hasanah; Khairurrijal, Khairurrijal; Tedi, Kurniawan; R., Mamat; Rina, Maryanti; Asep Bayu Dani, Nandiyanto; Hammouti, Belkheir (Elsevier Ltd, 2021)
Effects of electrolyte solution (i.e., KOH, NaOH, NaCl, and HCl) with various concentrations (from 0 to 0.71 M) on corrosion and mechanical properties of the copper alloys were investigated. Experimental results showed that the increases in the concentration of electrolytes allowed faster corrosion process. However, too high concentration of electrolytes has no further impacts on the corrosion profile due to the existence of the passivity phenomena on the surface of the material, preventing the material to get more corroded. Acidic (HCl) and salt (NaCl) electrolytes gave more impacts on the corrosion compared to the alkaline solution (i.e., NaOH and KOH) since the acidic and salt ions are able to destroy the formed passivation layer. The correlation of the corrosion rate and the mechanical properties was also presented, in which the increases in the corrosion rate were in line with the decreases in the mechanical properties (i.e., tensile and yield strength). During the corrosion, the atomic structure in the material received attacks from the electrolyte ions, making the structure inside the copper alloys to be less strong and easily fatigued. Understanding the corrosion process and mechanical properties is important for further applications of copper-related alloys in extreme and severe conditions.